Effects of an endurance cycling competition on resting serum insulin-like growth factor I (IGF-I) and its binding proteins IGFBP-1 and IGFBP-3 - Chicharro, J. L.; Lopez-Calderon, A.; Hoyos, J.; Martin-Velasco, A. I.; Villa, G.; Villanua, M. A.; Lucia, A. (British Journal of Sports Medicine, 2001)
OBJECTIVES:To determine whether consecutive bouts of intense endurance exercise over a three week period alters serum concentrations of insulin-like growth factor I (IGF-I) and/or its binding proteins. METHODS:Seventeen professional cyclists (mean (SEM) VO(2)MAX, 74.7 (2.1) ml/kg/min; age, 27 (1) years) competing in a three week tour race were selected as subjects. Blood samples were collected at each of the following time points: t(0) (control, before the start of competition), t(1) (end of first week), and t(3) (end of third week). Serum levels of both total and free IGF-I and IGF binding proteins 1 and 3 (IGFBP-1 and IGFBP-3) were measured in each of the samples. Cortisol levels were measured in nine subjects. RESULTS:A significant (p<0.01) increase was found in total IGF-I and IGFBP-1 at both t(1) and t(3) compared with t(o) (IGF-I: 110.9 (17.7), 186.8 (12.0), 196.9 (14.7) ng/ml at t(0), t(1), and t(3) respectively; IGFBP-1: 54.6 (6.6), 80.6 (8.0), and 89.2 (7.9) ng/ml at t(0), t(1), and t(3) respectively). A significant (p<0.01) decrease was noted in free IGF-I at t(3) compared with both t(o) and t(1) (t(0): 0.9 (0.1) ng/ml; t(1): 0.9 (0.1) ng/ml; t(3): 0.7 (0.1) ng/ml); in contrast, IGFBP-3 levels remained stable throughout the race. CONCLUSIONS:It would appear that the increase in circulating levels of both IGF-I and its binding protein IGFBP-1 is a short term (one week) endocrine adaptation to endurance exercise. After three weeks of training, total IGF-I and IGFBP-1 remained stable, whereas free IGF-I fell below starting levels.